Cross-Country Co-Movement between Bitcoin Exchanges: A Cultural Analysis - Guglielmo Maria Caporale; Woo-Young Kang (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper analyses co-movement between Bitcoin exchanges in 34 major countries around the world and the US (the global benchmark) over the period January 24, 2011 - January 7, 2019. More specifically, we run IV regressions to investigate the importance of cultural factors (such as tightness, individualism, trust and risk-taking) following an earlier study by Eun et al. (2015) which had shed light on their importance to explain stock co-movement within individual countries. The results suggest that markets in tighter, more individualistic, trustful and risk-taking societies are more tightly linked to the US one. Further, it appears that culturally looser, collectivistic, trustful and risk-taking countries are more likely to shut down their Bitcoin exchanges compared to other countries. These findings confirm our priors.
Keywords: G15; C36; 330; Bitcoin exchanges; cultural analysis; co-movement